2006
DOI: 10.1089/cbr.2006.21.225
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Adenovirus-Mediated E1A Gene Therapy Induces Tumor-Cell Apoptosis and Reduces Tumor Angiogenesis Leading to Inhibition of Hepatocellular Carcinoma Growth in Animal Model

Abstract: Oncolytic adenovirus (rAd)-mediated E1A gene therapy of cancer has become a novel therapeutic modality. In this study, we constructed a recombinant oncolytic adenovirus (rAd-E1A) expressing the tumor suppressor E1A gene. We demonstrated that the rAd-E1A replicated in HepG2 and SMMC-7721 human hepatocellular carcinoma (HCC) cells but attenuated in the normal liver cell line HL-7702. It induced HCC cell apoptosis through upregulation of apoptosis-associated Bax, caspase-3, and Fas and downregulation of survivin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The adenovirus vector is one of the most widely used vectors in gene therapy applications for the treatment of diverse human diseases including cancer (23). Ye et al (24) reported that adenovirus-mediated gene therapy demonstrated beneficial preclinical outcomes by inducing apoptosis of tumor cells and inhibiting tumor angiogenesis, which led to HCC regression in a HCC tumor model. Hu et al (25) revealed that adenovirus-mediated expression of melanoma differentiation-associated-7 efficiently inhibited HCC growth.…”
Section: Discussionmentioning
confidence: 99%
“…The adenovirus vector is one of the most widely used vectors in gene therapy applications for the treatment of diverse human diseases including cancer (23). Ye et al (24) reported that adenovirus-mediated gene therapy demonstrated beneficial preclinical outcomes by inducing apoptosis of tumor cells and inhibiting tumor angiogenesis, which led to HCC regression in a HCC tumor model. Hu et al (25) revealed that adenovirus-mediated expression of melanoma differentiation-associated-7 efficiently inhibited HCC growth.…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment of HCC, p53 products are injected into liver tissue by a variety of routes [55,72,82,[88][89][90][91][92] . When p53 products are injected intratumorally [55,88,89] , introduction of exogenous wt-p53 can inhibit cell growth, the expression of both p53 and p21 proteins is up-regulated in tumor cells. Intraarterial gene delivery into animal hepatic tumors can lead to selective gene expression in tumor cells [72] .…”
Section: Empirical Studies Of P53 Therapy For Hccmentioning
confidence: 99%
“…This gene transfer technique may have potential in clinical gene therapy for HCC. Oncolytic adenovirusmediated gene therapy induces tumor-cell apoptosis and reduces tumor angiogenesis, leading to inhibition of HCC growth in animal model [88] . Because CNHK200-mE is capable of selectively replicating in HCC cells, thus suppressing tumor growth and antiangiogenic activity in nude mice [85] , it can be used as a potential agent in the treatment of HCC.…”
Section: Empirical Studies Of P53 Therapy For Hccmentioning
confidence: 99%
“…E1A was also shown to stabilize c-Myc protein, the key regulator of cellular proliferation, by binding to p400, and this stabilization is critical for the ability of E1A to sensitize tumor cells to chemotherapy [27]. Moreover, it was demonstrated that E1A induced apoptosis in HCC cells by a p53-dependent pathway, in which E1A upregulated pro-apoptotic factors Bax, caspase-3, and Fas, and down-regulated anti-apoptosis factors survivin and Bcl-2 [28].…”
Section: Introductionmentioning
confidence: 99%